This man Jesus : the gospel narrative of his life and ministry - Harrell, Irene Burk.; Benson, Alie Harrell, 1954- (Grand Rapids, Mich. : Lamplighter Books, 1988)
Interweaves the gospels of Matthew, Mark, Luke, and John to present a retelling of the life of Jesus Christ.
Previous ed. published as: The manufacturer's handbook. c1987.
Includes index.
Keywords: Jesus Christ -- Biography -- Sources, Biblical; Jesus Christ; Bible stories -- N. T